Review: Effect of Material Characteristics, and Process Conditions in Reducing Gaseous Pollutants Using Fly Ash (FA)-Based Adsorbent - Setya Wardhana, Budi; Hanum, Farrah Fadhillah; Mufrodi, Zahrul; Jamilatun, Siti (Sains Natural: Journal of Biology and Chemistry, 2024)
The intensive use of fossil fuels has led to a significant increase in air pollution, which negatively affects human health and the environment. Fly ash (FA), a byproduct of coal combustion, has great potential as an adsorbent for hazardous gas pollutants due to its physical and chemical properties. This research aims to evaluate the effectiveness of fly ash as an adsorbent in reducing gas pollutants such as CO2, SO2, and NO2, as well as to examine the influence of temperature and material characteristics on adsorption capacity. The results indicate that the maximum adsorption capacity for each gas pollutant is achieved at different temperatures, fly ash demonstrating the highest performance at 150 °C for CO2 adsorption, achieving an efficiency of 94.7%. For SO2 and NO2, the optimum temperatures are 200 °C, with efficiencies of 72.17% and 100%, respectively. This study also emphasizes the importance of selecting the appropriate characteristics of the adsorbent material to enhance adsorption efficiency. This finding has the potential to support the development of more efficient and sustainable air pollution reduction technologies in the future, by utilizing industrial waste such as fly ash as an innovative solution.